Genomic and phenotypic polymorphism of Clostridium botulinum Group II strain Beluga through laboratory domestication - Selby, Katja; Douillard, François P.; Lindström, Miia (Elsevier Scientific Publ. Co, 2024)
Laboratory domestication is the result of genetic and physiological changes of organisms acquired during numerous passages in vitro. This phenomenon has been observed in bacteria as well as in higher organisms. In an effort to understand the impact of laboratory domestication on the foodborne pathogen Clostridium botulinum and related microbial food safety research, we investigated multiple spore stocks of C. botulinum Group II Beluga from our collection, as that is a widely applied model strain used in laboratories over decades. An acquired nutrient auxotrophy was confirmed as thymidine dependency using phenotypic microarrays. In parallel, whole-genome re-sequencing of all stocks revealed a mutation in thyA encoding thymidylate synthase essential for de-novo synthesis of dTMP from dUMP in the auxotrophic stocks. A thyA-deficient Beluga variant stock was successfully complemented by introducing an intact variant of thyA and thymidine prototrophy was restored, indicating that the thymidine auxotrophy was solely due to the presence of a SNP in thyA. Our data suggested that this mutation, deleterious under nutrient-poor growth conditions in a chemically defined medium, has been present and maintained in laboratory stocks for nearly 30 years. Yet, the mutation remained unidentified since receiving the strain, most likely due to routine use of culture conditions optimized for growth performance. This work pinpoints the need for careful monitoring of model strains extensively used in laboratory settings at both phenotypic and genomic level. In applications like food safety challenge tests, compromised strains could cause incorrect predictions and thereby have deleterious consequences. To mitigate the risk of acquiring mutations, we recommend keeping passage numbers of laboratory strains low and to avoid single-colony passaging. In addition, relevant strains should be subjected to regular WGS checks and physiological validation to exclude DNA mutations with potential negative impacts on research data integrity and ...